The Analysis of Employee Performance Affected by Organization Culture And Leadership With Job Satisfaction As Mediation - David irwanto Lumbantobing; Aris Budiono (Cita Konsultindo Research Center, 2023)
This article investigates the impact of Organizational Culture (X1), Leadership (X2), and Job Satisfaction (Y2) variables on employee performance (Y1) in service companies. The measurement instrument was based on the Likert scale, and a random sample of 30 participants was selected to ensure validity and reliability. For statistical analysis, we used a sample of 80 respondents and applied multiple linear regression with SPSS-25 to test the hypothesis of the simultaneous and partial effects of the variables. The Roscoe method was used to determine the sample size. The study's findings indicate that organizational culture has a positive relationship with job satisfaction, leadership has a positive impact on job satisfaction and employee performance, organizational culture does not directly affect employee performance, and job satisfaction has a positive effect on employee performance. Additionally, the study reveals that organizational culture indirectly impacts employee performance through job satisfaction, and leadership has no indirect effect on employee performance through job satisfaction.